PERBANDINGAN KEEFEKTIFAN TEKNIK RENCANA PRABACA DAN TEKNIK HUBUNGAN TANYA-JAWAB DALAM PEMAHAMAN BACAAN - Budyariesqa, Viera; Zuchdi, Darmiyati (Diksi, 2018)
(Title: Comparing the Effectiveness of Pre-Reading Plan (Prep) and Question-Answer Relationship (Qar) on The Reading Comprehension). This research aimed to find out which technique was the more effective among the Pre-Reading Plan (PreP), Question-Answer Relationship (QAR), and conventional technique in the reading comprehension. This research was quasi-experimental with pretest-posttest control group design. The population was all of the students of Grade VII Imogiri 3 JHS. The determination of sample using random sampling and was selected Grade VIIB as the experimental group 1 (PReP), Grade VIID as the experimental group 2 (QAR), and Grade VIIC as the control group (conventional technique). The instrument is a multiple choice test of reading comprehension based on reading standards of PISA 2015. Data were analyzed using one way ANOVA test and continued with Post Hoc Scheffe test with significance level of 0.05. The results of this study indicate PReP more effective than QAR and conventional techniques in the reading comprehension.Keywords: Pre-Reading Plan, Question-Answer Relationship, reading comprehension.